Misconduct as the main cause for retraction. A descriptive study of retracted publications and their authors - Isabel Campos-Varela; Alberto Ruano-Raviña (Elsevier, 2019)
Objective: To analyze the causes of retracted publications and the main characteristics of their authors. Method: A descriptive cross-sectional study was designed including all retracted publications from January 1st, 2013-December 31st, 2016 indexed in PubMed. The causes of retraction were classified as: data management, authorship issues, plagiarism, unethical research, journal issues, review process, conflict of interest, other causes, and unknown reasons. Then, misbehaviour was classified as misconduct, suspicion of misconduct or no misconduct suspicion. Results: 1,082 retracted publications were identified. The retraction rate for the period was 2.5 per 10,000 publications. The main cause of retraction was misconduct (65.3%), and the leading reasons were plagiarism, data management and compromise of the review process. The highest proportion of retracted publications corresponded to Iran (15.52 per 10,000), followed by Egypt and China (11.75 and 8.26 per 10,000). Conclusions: Currently, misconduct is the main cause of retraction. Specific strategies to limit this phenomenon must be implemented. It would be useful to standardize reasons and procedures for retraction. The development of a standard retraction form to be permanently indexed in a database might be relevant. Resumen: Objetivo: Analizar las causas de las retractaciones y las características fundamentales de sus autores. Método: Se diseñó un estudio descriptivo, transversal, que incluyó todas las publicaciones con retractación entre el 1 de enero de 2013 y el 31 de diciembre de 2016 indexadas en PubMed. Las causas de la retractación fueron clasificadas como manejo de datos, asuntos de autoría, plagio, investigación no ética, asuntos de las revistas, proceso de revisión, conflictos de intereses, otras causas y razones desconocidas. Tras esto, la conducta indebida fue clasificada como mala conducta, sospecha de mala conducta y sin sospecha de mala conducta. Resultados: Se identificaron 1.082 publicaciones retractadas. La proporción de publicaciones retractadas fue de 2,5 por cada 10.000 publicaciones para el periodo evaluado. La principal causa de retractación fue la mala conducta (65,3%), y las causas principales fueron plagio, manejo de los datos y compromiso del proceso de revisión. La mayor proporción de publicaciones retractadas correspondió a Irán (15,52 por 10.000), seguido de Egipto y China (11,75 y 8,26 por 10.000, respectivamente). Conclusiones: Actualmente, la mala conducta es la principal causa de retractación. Deberían implementarse estrategias específicas para limitar este fenómeno. Sería de utilidad uniformar los motivos y procedimientos para la retractación. Podría ser apropiado el desarrollo de un formulario estándar de retractación que sea indexado permanentemente en una base de datos. Keywords: Plagiarism, Peer review, Authorship, Fraud, Scientific misconduct, Palabras clave: Plagio, Revisión por pares, Autoría, Fraude, Mala conducta científica